2021
DOI: 10.1111/nyas.14690
|View full text |Cite
|
Sign up to set email alerts
|

A review of carbon farming impacts on nitrogen cycling, retention, and loss

Abstract: Soil carbon (C) sequestration in agricultural working lands via soil amendments and management practices is considered a relatively well‐tested and affordable approach for removing CO2 from the atmosphere. Carbon farming provides useful benefits for soil health, biomass production, and crop resilience, but the effects of different soil C sequestration approaches on the nitrogen (N) cycle remain controversial. While some C farming practices have been shown to reduce N fertilizer use in some cases, C farming cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…4 ), suggesting basalt provided inorganic nutrients in addition to raising soil pH. Significant yield increases in maize were only observed in those years of the rotation following soybean, suggesting an EW-nitrogen interaction ( 49 ). Extrapolated across the Corn Belt region, EW-related yield increases translate to ~$7-11 billion for maize, and $10 billion for soybean at current prices, indicating EW deployment could deliver substantial economic benefits for US agriculture through yield increases alone.…”
Section: Resultsmentioning
confidence: 99%
“…4 ), suggesting basalt provided inorganic nutrients in addition to raising soil pH. Significant yield increases in maize were only observed in those years of the rotation following soybean, suggesting an EW-nitrogen interaction ( 49 ). Extrapolated across the Corn Belt region, EW-related yield increases translate to ~$7-11 billion for maize, and $10 billion for soybean at current prices, indicating EW deployment could deliver substantial economic benefits for US agriculture through yield increases alone.…”
Section: Resultsmentioning
confidence: 99%
“…This multidimensional approach requires an absolute reduction in all types of greenhouse gases. The agricultural systems that promote soil carbon sequestration also stimulate nitrification and the subsequent release of nitrous oxide [528][529][530]. Nitrification inhibitors are a "double-edged sword" [15] that could promote ammonia emissions from soil [531].…”
Section: Agricultural Use Of the Recovered Biofertilizersmentioning
confidence: 99%
“…While non-legume species had a lower N concentration, legume CCs were able to maintain their concentration independently from the soil N availability, due to N fixation [83]. However, several studies showed as the soil N dynamic is strongly related not only to the botanical species but also to other several aspects that significantly contribute to N mineralization such as the termination method and time, weather conditions and soil characteristics [3,11,17,29,39]. Moreover, legumes are considered an essential choice for soil health management [84].…”
Section: Cover Crop Botanical Familymentioning
confidence: 99%
“…The increased carbon content transforms the soil into a carbon sink, thereby contributing to the reduction of carbon dioxide emissions, one of the main greenhouse gases. Therefore, the cultivation of CCs is proven to be a valuable tool for meeting the needs of carbon farming initiatives [29,30]. All these benefits represent specific functional outcomes to develop resilient agroecosystems able to sustain the main crop yield while preserving soil from climate change and extreme weather events such as flooding, drought, and variations in precipitation quantities and patterns.…”
Section: Introductionmentioning
confidence: 99%